Agricultural Productivity in Balochistan Province of Pakistan A Geographical Analysis - Ghulam Murtaza Safi,; Muhammad Sohail Gadiwala,; Farkhunda Burke,; Muhammad Azam,; Muhammad Fahad Baqa, (Journal of Basic & Applied Sciences, 2014)
Agricultural sector plays a leading role in Pakistan’s economy. It contributed to nearly one fifth of the national GDP in 2010. Agricultural productivity is regions dependent, demanding further investigation. This study examines the productivity index in districts of Balochistan province of Pakistan from 1981-82 to 2008-2009. Besides the thermal and water regime, pedological conditions play a favorable role in growing of valuable crops. The food crops, wheat, rice, bajra, barley jowar and maize have been selected for the study. By contrast, very low level of agricultural productivity is confined to the districts falling in the drought prone areas characterized by irregular rainfall, rugged topography and poor irrigation facilities. Inadequacy of water is the main hurdle in agricultural productivity. For the present investigation, district wise secondary data have been collected from the agricultural census of Balochistan. The data collected have been processed and Yield Coefficient method has been employed to find out the level of agricultural productivity. The results are depicted by choropleth method on map. Hence, in the present paper an attempt has been made to assess the regional disparities in levels of agricultural productivity in districts of Balochistan province. Identification of causes of the disparity can prove helpful in solving the problem, thus enabling solution of food security.